2020
DOI: 10.4103/ijcm.ijcm_397_19
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health of agricultural women workers in India

Abstract: Background: Women in Agriculture form a significant portion of the productive work force in Indian economy. Occupational Health is a vital component of nation's infrastructure and it focuses on the physical, mental and social well being of workers. In India, Occupational Heath among agricultural women is a public health issue which needs immediate attention. Objectives: To study the association between health and agriculture, the occupational hazards and health problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Suravi, S. / Occupational health hazards of women in agriculture -a study on Bargarh district of Odisha 48 Figure 2 revealed that in all the agricultural activities, physical hazards such as body pain (86.36%) and fatigue (83.63%) were most common, whereas 57.27%, 29.09% and 36.36% of respondents had headache, fever and infection, respectively. These were similar hazards faced by Meenakshi et al, 2020.…”
Section: Resultsmentioning
confidence: 83%
“…Suravi, S. / Occupational health hazards of women in agriculture -a study on Bargarh district of Odisha 48 Figure 2 revealed that in all the agricultural activities, physical hazards such as body pain (86.36%) and fatigue (83.63%) were most common, whereas 57.27%, 29.09% and 36.36% of respondents had headache, fever and infection, respectively. These were similar hazards faced by Meenakshi et al, 2020.…”
Section: Resultsmentioning
confidence: 83%
“…According to the National Institutes of Health, occupational health is an ongoing endeavor to safeguard and advance workers' highest level of mental, social, and physical well-being across all professions [ 26 ]. Despite having numerous laws and schemes for worker welfare in India, there is insufficient emphasis on the health aspects of female agricultural workers [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to the National Institutes of Health, occupational health is an ongoing endeavor to safeguard and advance workers' highest level of mental, social, and physical well-being across all professions [ 26 ]. Despite having numerous laws and schemes for worker welfare in India, there is insufficient emphasis on the health aspects of female agricultural workers [ 26 ]. The country conducted its first study assessing the incidence of employment discloses to numerous toxic agents, aiding in the ambulatory care provided by a reference center for agriculture labor health [ 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…2 In emerging nations, employees in the agricultural industry are under-protected compared to those in other industries, and they have a much higher rate of occupational diseases, accidents, and fatalities. 3 These workers endure unsafe work environments, pesticide exposure, long hours in hot weather, injuries from working with animals, and dangerous machinery. 4 Agricultural laborers are predisposed to occupational skin disease, among other health issues, as a result of their working environment.…”
Section: Introductionmentioning
confidence: 99%